Salamat sa wagas na pagmamahal - Bautista, Rosa Maria Juan ([Place of publicatin not identified Publisher not identified, 2014)
"This is the love story that touched the heart of the composer and inspired her to write this song: "Salamat sa Wagas na Pagmamahal." She felt God's love despite the destruction and the rubble because of the love story of Houssam Hammoudi and Grace Acojedo, a 23-year old Filipina. It is a love story that is stronger than the strongest and most destructive typhoon in History, Typhoon Yolanda (Haiyan). It is also a story that despite the destruction, the lives lost, the desperation of people, God is with us, and all over the world, people reached out to help. May this song be a tribute to God and the survivors of Yolanda."
Keywords: Songs with piano -- Scores